2022
DOI: 10.1186/s12645-022-00131-0
|View full text |Cite
|
Sign up to set email alerts
|

Improve the cytotoxic effects of megavoltage radiation treatment by Fe3O4@Cus–PEG nanoparticles as a novel radiosensitizer in colorectal cancer cells

Abstract: Background To enhance the performance of radiotherapy, emerging nanoparticles that can professionally enhance X-ray irradiation to destruct cancer cells are extremely necessary. Here, we examined the potential of PEG-coated magnetite copper sulfide hetero-nanoparticles (Fe3O4@Cus–PEG) as a radiosensitizer agent. Methods Fe3O4@Cus–PEG nanoparticles were synthesized and characterized. The toxicity of nanoparticles on HT-29 colorectal cancer cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Moreover, their effectiveness is still limited by the accumulation in tumor tissue and the poor effect of inducing TME, such as ROS. Therefore, there is an urgent need to further enhance their RT effect by precisely controlling the size and shape of nanoparticles or modifying their surface [ 40 , 58 , 61 ]. However, the preparation methods for these sensitizers are generally complicated, and their versatility is limited.…”
Section: Organelle-targeted Rtmentioning
confidence: 99%
“…Moreover, their effectiveness is still limited by the accumulation in tumor tissue and the poor effect of inducing TME, such as ROS. Therefore, there is an urgent need to further enhance their RT effect by precisely controlling the size and shape of nanoparticles or modifying their surface [ 40 , 58 , 61 ]. However, the preparation methods for these sensitizers are generally complicated, and their versatility is limited.…”
Section: Organelle-targeted Rtmentioning
confidence: 99%
“… 100 According to research, Fe3O4@Cus-PEG NPs are a promising nano radio-sensitizing agent, and the presence of nanoparticles enhanced the effects of X-ray radiation. 101 …”
Section: Radiosensitizers As Therapeutic Strategy In Rectal Cancermentioning
confidence: 99%
“…Radiosensitization of breast cancer to mega-voltage radiation therapy with PEG-coated gold-iron nanoparticles was increased under MV beams of 18 MV [ 84 ]. Mohammadian et al [ 85 ] suggested PEG-coated iron nanoparticles as promising nano-radiosensitizer in colorectal cancer treatment under 6-MV X-ray photons. Geng et al [ 11 ] demonstrated that glucose-coated gold NPs achieved superior enhancement ratios at 90 kVp than 6 MV.…”
Section: Physical Enhancementmentioning
confidence: 99%